Market Citizenship. - Root, Amanda (Sage Publications, 2007)
Citizens are caught in a paradox. Voting levels are falling, there are growing feelings of powerlessness, social unfairness and yet citizens are constantly told that they have more choice as well as greater freedom and liberty. This book brilliantly explains these discrepancies. It shows that the new definitions of freedom as responsibility to create prosperity through markets is seriously distorting citizenship whilst appearing to be unbiased and neutral. It exposes inconsistencies in the market-based and apolitical vision of our collective future. Key features of the book are:." Its th.